The demand for life insurance - Diacon, S.R. (1980)
This thesis is concerned with an examination of consumer purchases of life insurance. The problem is tackled in three main areas: first a theoretical examination of consumption, saving and bequest, based on the Yaari 'life-cycle' model of lifetime consumption. Secondly an analysis is developed to split new premium income into its two components: new savings and payments for protection against the financial effects of premature death. This analysis is then applied to the UK new business ordinary non-group renewable premium in order to derive figures for aggregate expenditure on savings-based and protection-based life insurance for the years 1946 to 1968. Thirdly, econometric techniques are applied to the aggregate data to explain the demand for both new and in force life insurance business: a study of the former is based on a single Demand and Supply model for new business (using the Two Stage Least Squares method); the analysis of contracts in force is undertaken by examining their Surrender Rates.